A culturally adapted psychologically informed, audiologist-delivered, manualized intervention for chronic tinnitus patients in Malaysia: Protocol for a randomized controlled feasibility trial - Mohamad Azmeer Sadali; Wan Syafira Ishak; Mahadir Ahmad; Derek J. Hoare (PLoS ONE, 2025)
Background Tinnitus, a phantom auditory perception, varies from mild awareness to intolerable sounds that can severely impact psychological well-being, sometimes leading to suicidal ideation. While its causality remains unclear, studies show a strong link between tinnitus severity and psychological distress. A manualized intervention developed in the United Kingdom for audiologists, using a low-intensity, psychologically informed approach, has been successfully trialed in Western populations. However, its feasibility in Asian settings, particularly in Malaysia with its diverse cultures, remains unknown. Methods Phase I involves three steps: (a) translating the intervention manual into Malay, (b) systematically adapting its content for cultural relevance, and (c) piloting the intervention. Phase II is a 4-month randomized controlled feasibility trial involving chronic tinnitus patients (n = 20), stratified by severity and randomly assigned to either (a) the adapted intervention delivered by a trained provider or (b) standard care. Feasibility outcomes include a 10% recruitment rate among eligible patients, a 65% eligibility rate within the target population, and 80% retention. Primary outcomes assess tinnitus severity via the Tinnitus Functional Index, while secondary outcomes measure psychological distress using the Depression Anxiety Stress Scale-42. Assessments occur at baseline, post-intervention (1 month), and at a 3-month follow-up. At follow-up, semi-structured interviews guided by the Theoretical Framework of Acceptability will explore participants’ perceptions of the intervention. Discussion This feasibility trial evaluates the practicality and acceptability of a culturally adapted, audiologist-delivered psychological intervention for chronic tinnitus patients in Malaysia. Unlike direct translations, it incorporates systematic cultural adaptation to ensure relevance for the target population. Findings will inform the viability of a future large-scale trial and the potential for expanding psychologically informed tinnitus care in audiology settings. Trial registration number ACTRN12624001048572